Análise do ruído e intervenção fonoaudiológica em ambiente escolar: rede privada e pública de ensino regular - Campos, Nara Batista De; Delgado-pinheiro, Eliane Maria Carrit (CEFAC Saúde e Educação, 2014)
Purpose : the aim of this study is to measure noise levels during the school year in two classrooms in a grade of elementary school, a private schools one and a public school another, in both case frequented by deaf students cochlear implant users, to analyze whether noise levels are consistent with the standard Brazilian NBR 10152 of ABNT (1990) and school staff to discuss strategies to minimize the impact of noise on learning of deaf students.Methods : we performed eight measurements of noise level, using a dosimeter, model 1444, in each classroom, in a private and public schools. At the same time the measurements were conducted with monthly meetings with teachers from both schools.Results : we found that levels of noise present in the public ranged from 74.3 to 79 dB (A) and in the private noise levels ranged between 76.1 and 80.9 dB (A). In each of these schools were made 8 meetings.Conclusion : after observations we found high levels of noise in the school environment, and there were no statistical differences between both networks. Referring to monthly meetings it was clear that educators have adopted strategies to help communication within the school environment. It´s clearly the need to acquire technological resource accessibility for deaf students who use oral communication, the system of modulated frequency.

Purpose: the aim of this study is to measure noise levels during the school year in two classrooms in a grade of elementary school, a private schools one and a public school another, in both case frequented by deaf students cochlear implant users, to analyze whether noise levels are consistent with the standard Brazilian NBR 10152 of ABNT (1990) and school staff to discuss strategies to minimize the impact of noise on learning of deaf students. Methods: we performed eight measurements of noise level, using a dosimeter, model 1444, in each classroom, in a private and public schools. At the same time the measurements were conducted with monthly meetings with teachers from both schools. Results: we found that levels of noise present in the public ranged from 74.3 to 79 dB (A) and in the private noise levels ranged between 76.1 and 80.9 dB (A). In each of these schools were made 8 meetings. Conclusion: after observations we found high levels of noise in the school environment, and there were no statistical differences between both networks. Referring to monthly meetings it was clear that educators have adopted strategies to help communication within the school environment. It´s clearly the need to acquire technological resource accessibility for deaf students who use oral communication, the system of modulated frequency.
Noise analysis and intervention in speech school environment: regular private and public schools
Keywords: Education; Noise; Cochlear Implant; Hearing Loss; Audiology; Educação; Ruído; Implante Coclear; Perda Auditiva; Audiologia